Effect of Wetting-Drying Cycle on the Deformation and Seepage Behaviors of Rock Masses around a Tunnel - Qingzhen Guo; Haijian Su; Hongwen Jing; Wenxin Zhu (Geofluids)
Water inrush caused by the wetting-drying cycle is a difficult problem in tunnel excavation. To investigate the effect of the wetting-drying cycle on the stability of the tunnel surrounding rock, physical experiments and numerical simulations regarding the process of tunnel excavation with different wetting-drying cycle numbers were performed in this study. The evolutions of stress, displacement, and pore water pressure were analyzed. With the increase in cycle number, the pore water pressure, vertical stress, and top-bottom approach of the tunnel surrounding rock increase gradually. And the increasing process could be divided into three stages: slightly increasing stage, slowly increasing stage, and sharply increasing stage, respectively. The failure process of the surrounding rock under the wetting-drying cycle gradually occurs from the roof to side wall, while the baseplate changes slightly. The simulation results showed that the maximum principal stress in the surrounding rock mass of the tunnel increases, while the minimum principal stress decreases. Furthermore, the displacement of the rock mass decreases gradually with the increasing distance from the tunnel surface. By comparing the simulation results with the experimental results, well consistency is shown. The results in this study can provide helpful references for the safe excavation and scientific design of a tunnel under the wetting-drying cycle.